Advances in Electronic Packaging, Parts A, B, and C 2005
DOI: 10.1115/ipack2005-73366
|View full text |Cite
|
Sign up to set email alerts
|

A Simulated and Experimental Comparison of Lead-Free and Tin-Lead Solder Interconnect Failure Under Impact Stimuli

Abstract: There is considerable reported evidence that a large percentage of failures which afflict portable electronic products are due to impact or shock during use. Failures of the external housing, internal electronic components, package-to-board interconnects, and liquid crystal display panels may occur as the result of accidental drops. Moreover, the introduction of lead-free solder to the electronics industry will bring additional design implications for future generations of mobile electronic systems. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has also been shown that the changes in the intermetallic morphology and the growth of Kirkendall voids due to thermal aging in SAC/OSP packages can lead to a transition in the failure site from solder to IMC/Cu interface [20]. For most plating materials, Sn-Pb solders have shown better durability than Pbfree solders [16,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that the changes in the intermetallic morphology and the growth of Kirkendall voids due to thermal aging in SAC/OSP packages can lead to a transition in the failure site from solder to IMC/Cu interface [20]. For most plating materials, Sn-Pb solders have shown better durability than Pbfree solders [16,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [15] were the first to report a transition in the failure site from solder to the intermetallic with increasing drop height during drop testing of PWAs. Heaslip et al [16] compared the drop durability of Sn37Pb and Sn95.5Ag3.8Cu0.7 solders and showed that the failure sites and failure mechanisms change with drop height and solder type; while Varghese and Dasgupta conducted high-speed bend tests and showed that the failure site transitions from the solder to the copper trace for specimens with Organic Solderability Preservative (OSP) finish [17,18]; and from the solder to the intermetallic compound (IMC) layer for specimens with Electroless Nickel/Immersion Gold (ENIG) finish [19]. Xu and Pang [20] conducted drop tests on thermally aged PWAs and showed that there were various failure sites even within the IMC layers.…”
Section: Introduction and Problem Statementmentioning
confidence: 98%
“…This change in failure site and in the failure mechanism caused the durability to vary non-monotonically with PWA strain rate, although it still varied monotonically with PWA strain amplitude. Heaslip et al [11] compared the drop durability of Sn-Pb and Pb-free solders and showed that the failure sites and failure mechanisms change with drop height and solder type.…”
Section: Introductionmentioning
confidence: 99%
“…al. [12] performed drop impact experiments using resistance monitoring of daisy chains consisting of pairs of solder joints. They reported sudden occurrence of failures over several drops.…”
Section: Introductionmentioning
confidence: 99%